Determination of polycyclic aromatic hydrocarbons using different extraction methods and HPLC-FLD detection in smoked and grilled meat products. (30th March 2022) - Onopiuk, Anna; Kołodziejczak, Klaudia; Marcinkowska-Lesiak, Monika; Poltorak, Andrzej
Highlights: Extraction method have a significant effect on the PAH level in meat. Smoking led to higher PAHs contamination in meat comparing to grilling. Benzo[ a ]anthracene was the most common PAH among meat samples. The most effective for PAHs analysis was method with saponification and SPE cleaning. Abstract: Polycyclic aromatic hydrocarbons (PAHs) in meat products are formed, among others, as a by-product of thermal processing such as smoking or grilling. Due their highly toxic effects on the human organism, it is necessary to monitor PAH content in food products and develop appropriate analytical methods for their determination. The aim of this study was to compare PAH content in meat products subjected to smoking or grilling process. PAH content was determined using three different analytical methods, verified for efficiency using the external standard method. The results showed that smoking led to higher PAH contamination compared to grilling. Extraction by saponification and SPE method was the most effective for the detection and quantification of PAHs. The samples analyzed using this method showed the highest PAH content and recoveries. The results of the study showed a significant effect of the extraction method on the recovery levels and PAH content in meat.